Confirming the Efficacy of an Adaptive Component to Family-Based Treatment for Adolescent Anorexia Nervosa: Study Protocol for a Randomized Controlled Trial - L’Insalata, Alexa; Trainor, Claire; Bohon, Cara; Mondal, Sangeeta; Le Grange, Daniel; Lock, James (Frontiers in Psychiatry, 2020)
Family-Based Treatment (FBT) has the largest evidence base for treating adolescents with anorexia nervosa (AN); 35 - 50% of cases remit at the end-of-treatment and remain remitted 3 - 4 years after treatment. Studies of FBT demonstrate that weight restoration by session 4 (of 2.4kgs) predicts remission at end of treatment in 85 - 90% of cases. One way to improve outcomes is to tailor treatments to patients depending on successful weight restoration at session 4. Pilot data found that by adding 3 sessions of Intensive Parental Coaching (IPC) after session 4 improved outcomes in early non-responders. Further, data suggest that the mechanism underlying FBT is early improvements in parental self-efficacy related to re-feeding their child. This manuscript describes a study protocol to examine whether adding IPC to FBT improves outcomes in early non-responders and confirm whether change in parental self-efficacy is the mechanism by which FBT works. This two-site randomized controlled trial (RCT) will randomize 60 adolescents with a DSM-5 diagnosis of AN (30 per site) who are between the ages of 12 - 18 years old and do not gain 2.4kgs by session 4 of FBT. Randomized participants will either continue standard FBT or receive the 3 sessions of IPC and then continue FBT as usual. Both arms include up to 18 sessions over the course of 9 months. Blinded assessments will be conducted at baseline, 3-month within-treatment, end of treatment, and at 6 and 12-month follow-up. Parental-self efficacy will be assessed using the Parent versus Anorexia Scale at all major assessment time points and at each of the first eight sessions of treatment. The primary outcome is achievement of weight remission (>94% expected mean percent BMI adjusted for age, height and gender). ClinicalTrials.gov Identifier: NCT03097874